Management of cognitive impairment associated with post-COVID-19 syndrome: recommendations for primary care - Zifko, Udo; Guendling, Katja; Seet, Raymond; Kasper, Siegfried (Frontiers in Pharmacology, 2024)
Introduction: Although post-COVID-19 syndrome (PCS) with cognitive impairment is increasingly encountered in primary care, evidence-based recommendations for its appropriate management are lacking. Methods: A systematic literature search evaluating the diagnosis and treatment of cognitive impairment associated with PCS was conducted. Practical recommendations for the management of PCS-associated cognitive impairment in primary care are summarized, based on an evaluation of pharmacological plausibility and clinical applications. Results: Currently, the pathology of cognitive impairment associated with PCS remains unclear with no high-quality data to support targeted interventions. Existing treatment approaches are directed towards symptom relief where counseling on the chronicity of the disease and regular reassessments at 4- to 8-week intervals is considered reasonable. Patients should be informed and encouraged to adopt a healthy lifestyle that centers around balanced nutrition and appropriate physical activities. They may also benefit from the intake of vitamins, micronutrients, and probiotics. The administration of Ginkgo biloba extract could offer a safe and potentially beneficial treatment option. Other non-pharmacological measures include physiotherapy, digitally supported cognitive training, and, if indicated, ergotherapy or speech therapy. In most patients, symptoms improve within 8 weeks. If serious, ambiguous, or when new symptoms occur, specialized diagnostic measures such as comprehensive neurocognitive testing or neuroimaging should be initiated. Very few patients would require inpatient rehabilitation. Conclusions: PCS with cognitive impairment is a debilitating condition that could affect daily functioning and reduce work productivity. Management in primary care should adopt a multidisciplinary approach, centering around physical, cognitive, and pharmacological therapies.